Effects of trunk girdlin on fruit production, fruit size and tree vigor on 'Bartlett' pears in Río Negro and Neuquén Valley, Argentina - Raffo Benegas, Maria Dolores; Calvo, Paula Cecilia; De Angelis, Veronica; Mañueco, María Lucía; Ziaurriz, Sergio Adrian; Menni, María Fernanda (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010